The modern colonization of the tropics: geography and planning in the first half of the 20th century - Nogueira, Carlo (Geografares, 2023)
To discuss the planned colonizing of tropical regions, we consider the approaches employed by particular geographers during the early 20th century, when geography was still a nascent discipline. The argument is presented in two sections. First, this paper will briefly examine how the colonization of territories that were considered vacant, particularly in tropical regions, became a relevant topic in a geography already preoccupied with global matters. Second, within the historical context of the 1950s, this study examines Brazilian geography's evaluation of territorial colonization policies implemented in the country at that time.
Keywords: history of geography; colonization; planning